Comparing The Effect Of Lactobacillus Aacidophilus And MRS Medium On Mesenchymal Stem Cells Proliferation - Mostafa Saberian; Elham Shahidi Delshad; Tahereh Naji; Ali Samadikuchaksaraei (Tehran University of Medical Sciences, 2015)
Background and Aim: The use of probiotics has been surveyed in different studies. For example, many researches have been conducted on immunity, cancer and embryonic cells proliferation. Mesenchymal stem cells (MSCs) have a rather slower growth and a more limited number of passages. In this research, the effect of supernatant of Lactobacillus acidophilus (LS) as one of the most commonly used probiotics on the proliferation of mesenchymal stem cells has been studied with the aim of increasing their proliferation for the treatment of patients in need of transplantation using mesenchymal stem cells. Materials and Methods: The MSCs separated from rats' bone marrow were led to bone and fat levels in the second passage, and their mesenchymal state was confirmed. The cells were then treated by the supernatant of Lactobacillus acidophilus (LS) and MRS broth medium, which have been separated in advance. The number of cells was examined by MTT test equated with the standard. Results: A curve was drawn for the cells' growth in different amounts and the number of cells was obtained by converting the results of MTT test to a standard curve. For statistical analyses, SPSS and ANOVA were employed. Conclusion: The findings show the double effect of LS on the weak effect of MRS broth medium. The use of supernatant of Lactobacillus acidophilus (LS) can be a practical and economical method for increasing the proliferation of MSCs isolated from bone marrow.